The contemporary state of Ukrainian tourism - Strizhnova, Marianna (My University, 2014)
Ukrainian tourism is now one of the fastest growing branches of the national economy. During the period of the Soviet Union, tourism was not even a branch of the State economy. It was just a neglected part of "the sphere of services". For a considerable length of time, foreign tourists were allowed to come to officially designated "open" cities only. Practically no soviet citizens were allowed to travel abroad. Український туризм зараз є однією з галузей національної економіки, що найшвидше розвиваються. За часів Радянського Союзу туризм навіть не був галуззю державної економіки. Він був лише занедбаною частиною «сфери послуг». Протягом значного часу іноземним туристам дозволялося відвідувати лише офіційно визначені «відкриті» міста. Практично жодному радянському громадянину не дозволялося подорожувати за кордон.
Keywords: tourism of Ukraine; туризм України; розвиток туризму; tourism development; кафедра іноземних мов професійного спрямування